Comparison of Plywood Export Competitiveness of Indonesia and China in The Asean+3 Market and Its Influencing Factors - Rustiadini, Milania; Novianti, Tanti (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Indonesia and China are the world's major exporters of plywood. ASEAN+3 is one of the plywood importing regions with a share of 20% so it is one of the plywood export destinations. Purpose: This has led to competition between the two countries in the plywood trade, especially the ASEAN+3 region. This study aims to analyze the comparison of Indonesia and China's plywood export competitiveness in the ASEAN+3 market and the factors that influence it. Design/methodology/approach: This study uses ten ASEAN+3 countries in the 2015-2022 period using the RCA, EPD, X-Model, and regression analysis methods. Findings/Result: The results of the RCA value of Indonesia and China are strongly competitive in the majority of ASEAN+3 countries. EPD shows Indonesia's plywood rising star position in seven countries and China's plywood rising star in only four countries. The X-Model method shows Brunei, Japan, South Korea, Thailand, and Vietnam have the potential to be optimistic markets for the development of Indonesian plywood exports, while Chinese plywood exports have the same potential in Malaysia, Myanmar, and Vietnam. Conclusion: It is concluded that Indonesia's plywood competitiveness is better than China's. Factors affecting Indonesia's plywood export volume are real GDP, population, export price, RCA value, and real exchange rate of the importing country.Originality/value (State of the art): Therefore, this study recommends several strategies such as market strengthening through certification and improving the quality of Indonesian plywood. Keywords: competitiveness, EPD, plywood, RCA, regression analysis